Ultralow-hardness polyurethane gel and preparation method thereof
By using highly reactive polyether polyols, ammonia nitrogen chain extenders and organic bismuth metal catalysts, ultra-low hardness polyurethane gels with moderate hardness were prepared, which solved the leakage of plasticizers of existing polyurethane gel materials, and the feel of not soft and greasy. The problem of poor stress dispersion has achieved widespread application of polyurethane gels in various application fields.
Patent Information
- Application Number
- CN202411604781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polyurethane gel materials have problems such as leakage of plasticizer, non-soft feel, poor stress dispersion and residual after use, which limits its wide application in medical care, electronics and sports products.
Using high-active macromolecular polyether polyol as the main chain, combined with chain extenders with ammonia nitrogen structure and organic bismuth metal catalyst, an ultra-low hardness polyurethane gel with a hardness of between 8 and 25 is prepared, with excellent flexibility, Stress dispersion ability and self-adhesive properties, and does not contain plasticizers.
It has achieved the effect of polyurethane gel without plasticizer leakage, soft and glutinous feel, good stress dispersion and residue-free, and is suitable for various application scenarios such as medical care, electronics and sports products.
Abstract
Description
Technical Field
[0001] The invention relates to a polyurethane gel and a preparation method thereof, and more specifically to an ultra-low hardness polyurethane gel and a preparation method thereof, and belongs to the field of polymer materials. Background Art
[0002] Polyurethane gel refers to a type of high molecular polymer with a three-dimensional network structure, which has been widely used in the fields of industry, medical treatment, beauty, construction and electronics in recent years. It is usually made by first synthesizing polyurethane oligomers with highly active polyether polyols and polyisocyanates, and then mixing them with active hydrogen substances (such as polyether polyols, polyester polyols, small molecule polyols, small molecule amino polyols, small molecule polyol amines, etc.) as macromolecular network structures, and then mixing them with chain extenders (such as small molecule alcohols, amino polyether polyols or diamines, etc.), catalysts (such as tertiary amines, quaternary ammonium salts, alkali metal carboxylates, transition metal weak acid salts, etc.) and other additives, and then manufacturing them into polyurethane gel materials through processes such as casting, spraying, compression molding and extrusion molding.
[0003] Compared with traditional silicone gel and rubber products, this type of polyurethane gel is usually given more application scenarios due to its excellent flexibility. However, in order to achieve this goal, traditional polyurethane gels usually use plasticizers, which inevitably lead to leakage. At the same time, in order to ensure the absolute flexibility of polyurethane gel products, there are often residues on the surface of the product after contact with the skin, and the flexibility and stress dispersion cannot meet the requirements at the same time, which greatly limits its application.
[0004] The Chinese patent with publication number CN 111333804 A discloses a polyurethane system for preparing skin-friendly polyurethane gel, which is a mixture of polyether polyol with ethylene oxide as the main polymerization monomer, modified MDI, catalyst and other additives if appropriately added, and can be used for leisure toys, mouse wrist rests, and can also be used for veneers such as pillow veneers, bicycle seat veneers, etc. At the same time, the preparation method of the polyurethane gel is simple and is conducive to production and use. However, due to the addition of plasticizers, plasticizer leakage will inevitably occur during its use, and it is not suitable for manufacturing products that come into direct contact with the skin. The Chinese patent with the publication number of CN 106063756A discloses a surgical combined position pad, comprising: a head fixing part, a cervical support and a shoulder pad, wherein the head fixing part, the cervical support and the shoulder pad are all made of polyurethane gel, and the polyether polyol 30-45 parts by weight is dissolved in a foaming agent 3-5 parts by weight, and then 0.05-0.2 parts by weight of carboxymethyl chitosan, 60-100 parts by weight of isocyanate and 0.5-1 parts by weight of a catalyst are added, and stirred for 15-20 minutes at 22-30° C.; 15-20 parts by weight of triethylamine are added, and the temperature is 35-40° C., nitrogen protection is applied, and the reaction is stirred for 0.5-1 hour; 10-20 parts by weight of a bacterial cellulose solution is added, and the bacterial cellulose content in the bacterial cellulose solution is 2-3wt%, and the temperature is 50-60° C., and the reaction is stirred for 1.5-2 hours, and the solution is left to stand, and freeze-dried to obtain the surgical pad. The surgical pad will not slide relative to each other during use, and has a good fixing effect, but the preparation process is complicated and not conducive to production.
[0005] In summary, the polyurethane gel materials currently on the market have problems such as plasticizer leakage, residues during use, and failure to meet stress dispersion requirements. Therefore, it is an urgent need for the industry to develop a polyurethane gel material that has no plasticizer leakage, a soft and elastic feel, and can disperse stress during use and has no residues. Summary of the invention
[0006] The present invention solves the deficiencies and problems existing in the above-mentioned prior art, and provides an ultra-low hardness polyurethane gel, which mainly uses high-activity macromolecular polyether polyol as the main chain of the polyurethane gel, giving it excellent flexibility; a chain extender with an ammonia nitrogen structure extends the chain and can accelerate the post-ripening process; an organic bismuth metal catalyst can effectively extend its operation time so that it meets the process requirements without shortening its subsequent curing time. The ultra-low hardness polyurethane gel has a hardness range between 8 and 25 in Shore A000, and has excellent properties such as stress dispersion support, viscoelasticity, no plasticizer addition, and self-adhesion. It can be widely used in body position support in the medical field, flexible packaging for shock absorption and energy absorption of precision instruments, and viscoelastic accessories for sports and leisure sports products.
[0007] The invention also provides a method for preparing the ultra-low hardness polyurethane gel. The preparation method is simple and easy to carry out under mild conditions.
[0008] The present invention is achieved through the following technical solutions:
[0009] The ultra-low hardness polyurethane gel of the present invention is composed of component A and component B, wherein the component A is an isocyanate-terminated polyurethane oligomer, which is prepared by mixing polyisocyanate and a high molecular weight polyether polyol containing an active hydrogen component reactive to an isocyanate group and performing a prepolymerization reaction, wherein the NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 2%-20%, wherein the mass amount of the polyisocyanate is 20-30 parts, and the mass amount of the high molecular weight polyether polyol is 70-80 parts;
[0010] The B component is composed of a high molecular weight polyether polyol, a chain extender and a catalyst, wherein the mass dosage of the high molecular weight polyether polyol is 80-99 parts, the mass dosage of the chain extender is 2-5 parts, and the mass ratio of the catalyst to the component B material is 0.1-0.5:10000;
[0011] When used, the mass ratio of components A and B is component A: component B = 10-30:100, and the mixture is evenly mixed to obtain an ultra-low hardness polyurethane gel.
[0012] The ultra-low hardness polyurethane gel of the present invention has a further technical solution that the NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 4%-15%; the polyisocyanate in component A is dodecyl 1,2-diisocyanate, hexamethylene diisocyanate (HDI), cyclohexane 1,3-diisocyanate, cyclohexyl isocyanate, hexahydrotoluene 2,4-diisocyanate, hexahydrophenyl 1,4-diisocyanate, perhydro-diphenylmethane 2,4-diisocyanate, phenylene 1,3-diisocyanate, phenylene 1,4-diisocyanate, 3,3-dimethyl 4, 4-diphenyl diisocyanate, toluene-2,4-diisocyanate (TDI), toluene-2,6-diisocyanate (TDI), stilbene-1,4-diisocyanate, 2,4'-diisocyanate (MDI), 4,4'-diisocyanate (MDI), naphthylene-1,5-diisocyanate (NDI), 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate or a combination thereof; the high molecular weight polyether polyol described in component A has a functionality between 2 and 6 and a hydroxyl value between 9.4 and 168 mg The invention relates to a polyether polyol having a functionality between 2 and 4 and a hydroxyl value between 27.5 and 56 mg KOH / g, and using glycerol, trimethylolpropane, propylene glycol, dipropylene glycol or tripropylene glycol or a combination thereof as an initiator, and a polyether polyol having an ethylene oxide end-capping ratio between 13% and 23%, and the amount thereof is 90 to 98 parts. The chain extender described in the B component is one or more of a small molecule alcohol, an amino polyether polyol or a diamine chain extender. The catalyst described in the B component is one or more of an amine catalyst and an organic metal catalyst or a combination thereof.A further technical solution is that the NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 6%-8%; the polyisocyanate in component A is one of 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate or 4,4'-diphenylmethane diisocyanate or a combination thereof; the high molecular weight polyether polyol in component A is an initiator of one of glycerol, propylene glycol and dipropylene glycol or a mixture thereof, with a functionality between 2 and 3 and a hydroxyl value of 27.5-56 mg The invention discloses a high molecular weight polyether polyol having a KOH / g content and an ethylene oxide end-capping ratio of 15-20%; the functionality of the high molecular weight polyether polyol described in component B is between 2 and 3; the chain extender described in component B is one or a combination of 1,4-butanediol, ethylene glycol, propylene glycol, triethanolamine or polyether polyol initiated by ethylenediamine or diethyltoluenediamine; the catalyst is one or a combination of triethylenediamine, bis(dimethylamino)ethyl ether, N-ethylmorpholine, N,N-dimethylcyclohexylamine, N,N-dimethylethanolamine, 4-methylbutanediamine, triethylamine, stannous octoate, dibutyltin dilaurate, zinc octoate, organic bismuth metal catalyst, methyl acetate, dioctyltin dimercaptoacetate, and cobalt cyclohexaneate. A further technical solution is that the chain extender is a polyether polyol initiated by ethylenediamine, with a functionality of 4 and a hydroxyl value between 450-770 mg KOH / g; the catalyst is triethylenediamine or an organic bismuth metal catalyst or a combination thereof. A further technical solution can also be that the polyisocyanate is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, and 2,2'-diphenylmethane diisocyanate in a mass ratio of 42-50:49-56:1-2. 6. The ultra-low hardness polyurethane gel according to claim 2 is characterized in that the prepolymerization reaction temperature is 80±2°C and the reaction time is more than 3 hours; the mass ratio of the two components A and B is component A: component B = 15-25:100.
[0013] The method for preparing the ultra-low hardness polyurethane gel of the present invention comprises the following steps:
[0014] (1) uniformly mixing polyisocyanate and high molecular weight polyether polyol according to a certain proportion to obtain component A;
[0015] (2) uniformly mixing a high molecular weight polyether polyol, a chain extender and a catalyst in proportion to obtain component B;
[0016] (3) Component A and component B are mixed evenly in a double mixing homogenizer according to a certain proportion, poured into a mold for curing and molding, and an ultra-low hardness polyurethane gel is obtained.
[0017] The method for preparing the ultra-low hardness polyurethane gel of the present invention further comprises the following steps:
[0018] (1) Mixing polyisocyanate and high molecular weight polyether polyol in proportion, raising the temperature to 80±2° C., reacting for more than 3 hours at this temperature, then cooling to below 35° C., and evacuating at a vacuum degree of 0.1 MPa for more than 1 hour to obtain component A;
[0019] (2) mixing a high molecular weight polyether polyol and a chain extender in a uniform proportion, stirring and heating to 100-110° C., dehydrating under vacuum at a vacuum degree of 0.1 MPa for more than 2 h, then cooling to below 35° C., adding a catalyst diluted with the high molecular weight polyether polyol, and degassing under vacuum for more than 1 h to obtain component B;
[0020] (3) Component A and component B are mixed evenly in a double mixing homogenizer according to a certain proportion, and then the mixed solution is poured into a mold, first cured at room temperature for more than 3 hours, and then aged at 45-55°C for more than 8 hours to react and form an ultra-low hardness polyurethane gel.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The ultra-low hardness polyurethane gel of the present invention adds a certain proportion of ammonia nitrogen group-containing chain extender in the formula, which significantly accelerates the surface drying time while providing softness comparable to that of plasticizers. At the same time, the high molecular weight polyether in the formula not only forms a polymer network skeleton, but also gives the product a soft, waxy and elastic performance, so that the product provides considerable stress dispersion during use. In addition, since the present invention does not contain any form of plasticizer, precipitation will not occur.
[0023] The ultra-low hardness polyurethane gel product of the present invention has a hardness between Shore A000 reading 8 and Shore A00 reading 25; its operable time (flow time) at 25°C is ≤1.5h, and its surface drying time is ≤3h; it is applied in the medical field, such as head pads, stretcher pads, operating room table pads, surgical cover pads, arm pads, shoulder pads, elbow pads, leg pads, ankle pads, foot pads, chest, trunk and hip positioners, wheelchair cushions, adaptive pads and hand exercisers, etc.; in the flexible packaging field of shock absorption and energy absorption of precision instruments, such as surface packaging of flexible sensors, fixing and sealing of precision electronic components; accessories of sports and leisure sports products, such as turning fixtures of polyurethane wear-resistant elements, soles driven by polyurethane shock-absorbing cavities, polyurethane elastic sports field materials, polyurethane sports underwear and bicycle shock-absorbing saddles, etc. DETAILED DESCRIPTION
[0024] The present invention is described below by means of specific examples, but the present invention is not limited to these examples.
[0025] The terms and test methods used in the present invention have the following definitions or explanations:
[0026] "Functionality" refers to the value obtained by measuring according to the industry formula: functionality = hydroxyl value * molecular weight / 56100; wherein the molecular weight is measured by GPC high performance liquid chromatography, and the test method refers to GB / T 21863-2008.
[0027] The "hydroxyl number" denotes the amount of potassium hydroxide in milligrams which is equivalent to the amount of acetic acid which is bound when acetylation is effected on 1 gram of substance. In the context of the present invention, it is determined in accordance with standard DIN 53240-2 (1998).
[0028] "NCO content" refers to the content of NCO groups in the system, measured at room temperature according to GB / T 12009.4-2016.
[0029] "Surface drying time" refers to the time from the mixing of the reaction components to the basic formation at room temperature.
[0030] "Operable time", also referred to as flow time, refers to the time from when the components of the reaction system are stirred evenly to when the viscosity reaches 600mPa.S. The operable time of the present invention is measured by the following method: the components of the polyurethane reaction system are respectively thermostated at 35 degrees Celsius, and then the components are mixed in the required proportions, stirred for 1 minute until the mixture is evenly mixed, and kept at 35 degrees Celsius, and the viscosity is measured once every 3 minutes with a viscometer, and the time required until the viscosity of the reaction system reaches 600mPa.S is recorded, which is the operable time.
[0031] "A00" hardness refers to the reading measured vertically on the sample surface using a Shore A00 hardness tester.
[0032] "A000" hardness refers to the reading measured vertically on the sample surface using a Shore A000 hardness tester.
[0033] Example 1
[0034] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 25.5 parts of the isocyanate component and 74.5 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35°C, and vacuumed for 1 hour at a vacuum degree of 0.1 MPa to obtain component A.
[0035] 96 parts of polyether polyol (B-1) and 3.6 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.4 parts of catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 18.5:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0036] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 42:56:2; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0037] The performances are shown in Table 1.
[0038] Example 2
[0039] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 29.67 parts of the isocyanate component and 70.33 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 81 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35°C and vacuum degassed for 1 hour to obtain component A.
[0040] 96 parts of polyether polyol (B-1) and 3.6 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.4 parts of catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 25:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed solution into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0041] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 49:49:2; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 20%, the functionality is 2, and the hydroxyl value is 56 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 13%, the functionality is 3, and the hydroxyl value is 27.5 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 450 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0042] The performances are shown in Table 1.
[0043] Example 3
[0044] 23.69 parts of isocyanate component and 76.31 parts of polyether polyol (A-2) containing reactive hydrogen atoms were added to a 500 ml round-bottom flask equipped with a stirrer and a thermometer, and the temperature was slowly raised to 79 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed for degassing for 1 hour to obtain component A.
[0045] 96 parts of polyether polyol (B-1) and 3.6 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.4 parts of catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 15:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0046] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 50:49:1; the polyether polyol A-2 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 17%, the functionality is 3, and the hydroxyl value is 34 mg KOH / g; the polyether polyol B-1 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 770 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0047] The performances are shown in Table 1.
[0048] Example 4
[0049] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 28.35 parts of the isocyanate component and 71.65 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0050] 96.7 parts of polyether polyol (B-1) and 3 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added 0.3 parts of a catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 18.5:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0051] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 45:54:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 17%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 21%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0052] The performances are shown in Table 1.
[0053] Example 5
[0054] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 28.25 parts of the isocyanate component and 71.75 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0055] Add 96 parts of polyether polyol (B-1) and 3.5 parts of chain extender (B-2) to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stir and heat to 105°C, vacuum dehydrate for 2h at a vacuum degree of 0.1MPa, then cool to 35°C, add 0.5 parts of catalyst diluted to 2% with B-1, and vacuum degas for 1h to obtain component B. According to the mass ratio of component A: component B = 19:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, then pour the mixed solution into the mold, first cure at room temperature for 3h, and then mature at 50°C for 8h for reaction molding.
[0056] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 43:55.5:1.5; the polyether polyol A-2 uses tripropylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 18%, the functionality is 2, and the hydroxyl value is 46 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 450 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0057] The performances are shown in Table 1.
[0058] Example 6
[0059] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 25.5 parts of the isocyanate component and 74.5 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0060] 96 parts of polyether polyol (B-1) and 3.5 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.5 parts of a catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 18.5:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0061] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 47:52:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 450 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0062] The performances are shown in Table 1.
[0063] Example 7
[0064] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 29.67 parts of the isocyanate component and 70.33 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0065] 95.9 parts of polyether polyol (B-1) and 4 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C, added 0.1 parts of a catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 19:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0066] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 43:56:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 56 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0067] The performances are shown in Table 1.
[0068] Comparative Example 1
[0069] 25.5 parts of isocyanate component and 74.5 parts of polyether polyol (A-2) containing hydrogen atoms reactive thereto were added to a 500 ml round-bottom flask equipped with a stirrer and a thermometer, and the temperature was slowly raised to 50 degrees Celsius while stirring. After reacting for 5 hours, the temperature was lowered to 35 degrees Celsius to obtain component A.
[0070] Add 96 parts of polyether polyol (B-1) and 3.6 parts of chain extender (B-2) to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stir and heat to 105°C, cool to 35°C, add 0.4 parts of catalyst diluted to 2% with B-1, and obtain component B. According to the mass ratio of component A: component B = 13:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3h, and then mature at 50°C for 8h for reaction molding.
[0071] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate in a mass ratio of 45:55; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0072] The performances are shown in Table 1.
[0073] Comparative Example 2
[0074] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 25.5 parts of the isocyanate component and 74.5 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35°C, and vacuumed for 1 hour at a vacuum degree of 0.1 MPa to obtain component A.
[0075] 96 parts of polyether polyol (B-1) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, and then vacuum-dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.4 parts of catalyst diluted to 2% with B-1, and then vacuum-degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 20:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed solution into a mold, and mature at 50°C for 8 hours for reaction molding.
[0076] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 42:56:2; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; and the catalyst is an organic bismuth metal catalyst.
[0077] The performances are shown in Table 1.
[0078] Comparative Example 3
[0079] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 25.5 parts of the isocyanate component and 74.5 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35°C, and vacuumed for 1 hour at a vacuum degree of 0.1 MPa to obtain component A.
[0080] 96 parts of polyether polyol (B-1) and 3.6 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, and the mixture was stirred and heated to 105°C, and then vacuumed and dehydrated for 2 hours at a vacuum degree of 0.1MPa, and then cooled to 35°C to obtain component B. According to the mass ratio of component A: component B = 18.5:100, components A and B were weighed with a dedicated SPEEDMIXER mixing cup, mixed at 1000rpm for 60 seconds using a SPEEDMIXER mixer, and then the mixture was poured into the mold, first cured at room temperature for 3 hours, and then aged at 50°C for 8 hours for reaction molding.
[0081] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 46:53:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0082] The performances are shown in Table 1.
[0083] Comparative Example 4
[0084] 23.69 parts of isocyanate component and 76.31 parts of polyether polyol (A-2) containing reactive hydrogen atoms were added to a 500 ml round-bottom flask equipped with a stirrer and a thermometer, and the temperature was slowly raised to 79 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed for degassing for 1 hour to obtain component A.
[0085] 95.4 parts of polyether polyol (B-1) and 1 part of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added 0.4 parts of catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 19:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0086] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 50:49:1; the polyether polyol A-2 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 17%, the functionality is 3, and the hydroxyl value is 34 mg KOH / g; the polyether polyol B-1 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 770 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0087] The performances are shown in Table 1.
[0088] Comparative Example 5
[0089] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 29.67 parts of the isocyanate component and 70.33 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0090] 95.9 parts of polyether polyol (B-1) and 4 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added 0.1 parts of a catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 32:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed solution into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0091] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate in a mass ratio of 42:58; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 56 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0092] The performances are shown in Table 1.
[0093] Comparative Example 6
[0094] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 25.5 parts of the isocyanate component and 74.5 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0095] 96 parts of polyether polyol (B-1) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, and then vacuum-dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added with 0.4 parts of a catalyst diluted to 2% with B-1, and then vacuum-degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 18.5:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0096] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 47:52:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 15%, the functionality is 2, and the hydroxyl value is 28 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 23%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the catalyst is a composite catalyst, triethylenediamine: organic bismuth metal catalyst = 1:5.
[0097] The performances are shown in Table 1.
[0098] Comparative Example 7
[0099] In a 500 ml round-bottom flask equipped with a stirrer and a thermometer, 40.82 parts of the isocyanate component and 59.18 parts of the polyether polyol (A-2) containing reactive hydrogen atoms were added respectively, and the temperature was slowly raised to 80 degrees Celsius while stirring. After reacting for 3 hours, the temperature was lowered to 35 degrees Celsius and vacuumed and degassed for 1 hour to obtain component A.
[0100] 96.7 parts of polyether polyol (B-1) and 3 parts of chain extender (B-2) were added to a 1000ml round-bottom flask equipped with a stirrer and a thermometer, stirred and heated to 105°C, vacuum dehydrated for 2 hours at a vacuum degree of 0.1MPa, then cooled to 35°C and added 0.3 parts of a catalyst diluted to 2% with B-1, and then vacuum degassed for 1 hour to obtain component B. According to the mass ratio of component A: component B = 18.5:100, weigh components A and B with a dedicated SPEEDMIXER mixing cup, use a SPEEDMIXER mixer to mix at 2000rpm for 60 seconds, and then pour the mixed liquid into the mold, first cure at room temperature for 3 hours, and then mature at 50°C for 8 hours for reaction molding.
[0101] The isocyanate component is a mixture of 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 45:54:1; the polyether polyol A-2 uses propylene glycol as an initiator, the ethylene oxide end-capping mass ratio is 17%, the functionality is 2, and the hydroxyl value is 56 mg KOH / g; the polyether polyol B-1 uses glycerol as an initiator, the ethylene oxide end-capping mass ratio is 21%, the functionality is 3, and the hydroxyl value is 28 mg KOH / g; the chain extender is a polyether polyol (B-2) initiated by ethylenediamine, the functionality is 4, and the hydroxyl value is 640 mg KOH / g; the catalyst is an organic bismuth metal catalyst.
[0102] The performances are shown in Table 1.
[0103] The test results of the embodiments and comparative examples are shown in Table 1
[0104] Flow time (h) Surface drying time (h) Shore A000 hardness Shore A00 hardness Example 1 1 2 26 0 Example 2 1 1.5 Reach range 25 Example 3 1 1.6 15 0 Example 4 1.2 1.5 30 0 Example 5 0.7 1.4 Reach range 5 Example 6 0.8 1.6 34 0 Example 7 0.9 1.3 40 0 Comparative Example 1 +∞ Uncured Uncured Uncured Comparative Example 2 1.5 4 30 0 Comparative Example 3 +∞ Uncured Uncured Uncured Comparative Example 4 2 +∞ Uncured Uncured Comparative Example 5 0.8 1.5 Reach range 50 Comparative Example 6 1.2 5.1 30 0 Comparative Example 7 0.8 1.5 Reach range 55
[0105] Note: +∞ means infinite time; after the Shore A000 reaches the test range, use Shore A00 for testing again.
[0106] Experiments show that, compared with the comparative example, the polyether polyol chain extender added by the present invention can effectively shorten the curing time of the reaction system, and the synergistic participation of the organic metal catalyst can effectively prolong the flow operable time of the reaction system without affecting the post-curing compared with the tertiary amine catalyst; the prepared polyurethane gel not only has a certain stress dispersion ability but also has a soft and elastic touch, without the precipitation of plasticizer, and can fully meet the needs of different application scenarios.
Claims
1. An ultra-low hardness polyurethane gel, consisting of component A and component B, characterized in that: The component A is an isocyanate-terminated polyurethane oligomer, which is prepared by mixing a polyisocyanate and a high molecular weight polyether polyol containing an active hydrogen component reactive to an isocyanate group and performing a prepolymerization reaction. The NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 2%-20%, wherein the mass amount of the polyisocyanate is 20-30 parts, and the mass amount of the high molecular weight polyether polyol is 70-80 parts; The B component is composed of a high molecular weight polyether polyol, a chain extender and a catalyst, wherein the mass dosage of the high molecular weight polyether polyol is 80-99 parts, the mass dosage of the chain extender is 2-5 parts, and the mass ratio of the catalyst to the component B material is 0.1-0.5:10000; When used, the mass ratio of components A and B is component A: component B = 10-30:100, and the mixture is evenly mixed to obtain an ultra-low hardness polyurethane gel.
2. The ultra-low hardness polyurethane gel according to claim 1, characterized in that: The NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 4%-15%; the polyisocyanate in component A is dodecyl 1,2-diisocyanate, hexamethylene diisocyanate (HDI), cyclohexane 1,3-diisocyanate, cyclohexyl isocyanate, hexahydrotoluene 2,4-diisocyanate, hexahydrophenyl 1,4-diisocyanate, perhydro-diphenylmethane 2,4-diisocyanate, phenylene 1,3-diisocyanate, phenylene 1,4-diisocyanate, 3,3-dimethyl 4,4-diphenyl diisocyanate, toluene ~2,4~diisocyanate (TDI), toluene~2,6~diisocyanate (TDI), distyrene 1,4~diisocyanate, 2,4'~diisocyanate (MDI), 4,4'~diisocyanate (MDI), naphthylene~1,5~diisocyanate (NDI), 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate or a combination thereof; the high molecular weight polyether polyol described in component A has a functionality between 2 and 6 and a hydroxyl value between 9.4 and 168 mg The invention relates to a polyether polyol having a functionality between 2 and 4 and a hydroxyl value between 27.5 and 56 mg KOH / g, and using glycerol, trimethylolpropane, propylene glycol, dipropylene glycol or tripropylene glycol or a combination thereof as an initiator, and a polyether polyol having an ethylene oxide end-capping ratio between 13% and 23%, and the amount thereof is 90 to 98 parts. The chain extender described in the B component is one or more of a small molecule alcohol, an amino polyether polyol or a diamine chain extender. The catalyst described in the B component is one or more of an amine catalyst and an organic metal catalyst or a combination thereof.
3. The ultra-low hardness polyurethane gel according to claim 2, characterized in that: The NCO mass ratio of the isocyanate-terminated polyurethane oligomer is 6%-8%; the polyisocyanate in component A is one of 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate or 4,4'-diphenylmethane diisocyanate or a combination thereof; the high molecular weight polyether polyol in component A is an initiator of one of glycerol, propylene glycol and dipropylene glycol or a mixture thereof, with a functionality between 2 and 3 and a hydroxyl value of 27.5-56 mg The invention discloses a high molecular weight polyether polyol having a KOH / g content and an ethylene oxide end-capping ratio of 15-20%; the functionality of the high molecular weight polyether polyol described in component B is between 2 and 3; the chain extender described in component B is one or a combination of 1,4-butanediol, ethylene glycol, propylene glycol, triethanolamine or polyether polyol initiated by ethylenediamine or diethyltoluenediamine; the catalyst is one or a combination of triethylenediamine, bis(dimethylamino)ethyl ether, N-ethylmorpholine, N,N-dimethylcyclohexylamine, N,N-dimethylethanolamine, 4-methylbutanediamine, triethylamine, stannous octoate, dibutyltin dilaurate, zinc octoate, organic bismuth metal catalyst, methyl acetate, dioctyltin dimercaptoacetate, and cobalt cyclohexaneate.
4. The ultra-low hardness polyurethane gel according to claim 3, characterized in that: The chain extender is a polyether polyol initiated by ethylenediamine, with a functionality of 4 and a hydroxyl value between 450-770 mg KOH / g; the catalyst is triethylenediamine or an organic bismuth metal catalyst or a combination thereof.
5. The ultra-low hardness polyurethane gel according to claim 3, characterized in that: The polyisocyanate is prepared by mixing 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate and 2,2'-diphenylmethane diisocyanate in a mass ratio of 42-50:49-56:1-2.
6. The ultra-low hardness polyurethane gel according to claim 2, characterized in that: The prepolymerization reaction temperature is 80±2°C, and the reaction time is more than 3 hours; the mass ratio of the two components A and B is component A: component B = 15-25:
100.
7. A method for preparing the ultra-low hardness polyurethane gel according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) uniformly mixing polyisocyanate and high molecular weight polyether polyol according to a certain proportion to obtain component A; (2) uniformly mixing a high molecular weight polyether polyol, a chain extender and a catalyst in proportion to obtain component B; (3) Component A and component B are mixed evenly in a double mixing homogenizer according to a certain proportion, poured into a mold for curing and molding, and an ultra-low hardness polyurethane gel is obtained.
8. The method for preparing the ultra-low hardness polyurethane gel according to claim 7, characterized in that: The following steps are involved: (1) Mixing polyisocyanate and high molecular weight polyether polyol in proportion, raising the temperature to 80±2° C., reacting for more than 3 hours at this temperature, then cooling to below 35° C., and evacuating at a vacuum degree of 0.1 MPa for more than 1 hour to obtain component A; (2) mixing a high molecular weight polyether polyol and a chain extender in a uniform proportion, stirring and heating to 100-110° C., dehydrating under vacuum at a vacuum degree of 0.1 MPa for more than 2 h, then cooling to below 35° C., adding a catalyst diluted with the high molecular weight polyether polyol, and degassing under vacuum for more than 1 h to obtain component B; (3) Component A and component B are mixed evenly in a double mixing homogenizer according to a certain proportion, and then the mixed solution is poured into a mold, first cured at room temperature for more than 3 hours, and then aged at 45-55°C for more than 8 hours to react and form an ultra-low hardness polyurethane gel.
Citation Information
Patent Citations
Combined type body posture pad for operation
CN106063756A
Polyurethane system for preparing skin-friendly polyurethane gel
CN111333804A